Ergodicity of CIR type SDEs driven by stable processes with random switching. Issue 5 (3rd July 2020) - Zhang, Zhenzhong; Cao, Jingwen; Tong, Jinying; Zhu, Enwen
Abstract : In this paper, we focus on ergodicity and transience of the Cox–Ingersoll–Ross interest rate model driven by stable processes with random switching. Under some assumptions, we prove that the interest rate process and switching process has a unique stationary distribution. In addition, some sufficient conditions for transience of such interest rate model are given.